Сreativity of a future teacher personality as a scientific category: historical and theoretical analysis - Odarchenko, Veronika; Repko, Inna; Stepanets, Ivan (My University, 2021)
The scientific article is devoted to the historical and theoretical study of the phenomenon of creativity of the individual, in particular the student in the context of future pedagogical activity, based on such concepts as "personality", "creativity", "creative potential", "creative abilities", "pedagogical creativity". Approaches and author's understanding of basic concepts are clarified. Analysis of the results of scientific research and the content of publications made by philosophers, psychologists, educators in their historical retrospect testified the existence of various theories and concepts of personality as a creative individual in ancient and Christian philosophy, in the Enlightenment, in Western philosophy XIX - early XX century, in the twentieth century and so far. The most important result of the scientific research is the establishment of the social conditioning of creativity, in particular the determination of its formation and development by socio and cultural values, professional needs, social activity. Categories of creativity are presented in philosophical, psychological and pedagogical senses, an attempt to compare them is made. The generalizing characteristics of the creative personality concerning its individuality, creative potential, readiness for creative activity are listed in the article. The authorial vision of logic and interrelation of structural components of formation and development of creative personality which is to provide the unity of conditions and means for realization of creative potential of the personality of a future teacher in educational process (training, practice, extracurricular work) is presented. The main results of the study include the establishment of approaches to the problem of creative abilities of the individual, the strategy of creative activity and components of the creative potential of the individual as its systemic characteristics. Generalization of scientific concepts creates a sense of specificity of approaches to defining key categories of creativity and allows to determine their essential characteristics, which creates conditions for a more conscious and effective construction of the educational process, in particular in pedagogical institutions of higher education.
Odarchenko V. Сreativity of a future teacher personality as a scientific category: historical and theoretical analysis / V. Odarchenko, I. Repko, I. Stepanets // Modernization of the pedagogical system of tertiary education in higher education institutions: collective monograph/ edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko and other ; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council. – Kharkiv : Publishing house Education and Science s.r.o., 2021.– Р. 51–76.
Keywords: особистість, творчість, творчий потенціал, педагогічна творчість, формування, розвиток, творча особистість, творча діяльність; personality, creativity, creative potential, pedagogical creativity, formation, development, creative personality, creative activity